High Expectations, Low Outcomes: Exploring Coping Mechanisms and Psychological Adaptation - Madhvi Prasad (International Journal of Trends in Humanities, 2025)
This review paper explores the psychological impact of high expectations and low outcomes, focusing on coping mechanisms to manage the resulting emotional and mental challenges. The anticipation of a guaranteed future often elevates self-esteem and brings a state of emotional ecstasy. When individuals perceive the future in alignment with their personal terms and conditions, they experience heightened happiness and acceptance of life. This sense of assurance often influences risk-taking capacity, leading individuals to be less calculative and strategic in their decision-making processes. A study by Damen (2019) found that when outcomes are certain and not delayed, the tendency to take risks is higher. While both genders exhibit interest in future expectations, differences arise in how they handle outcomes. Setting high expectations for a goal is a positive psychological indicator of commitment. However, the adverse effects of unmet expectations must be studied to address the psychological distress they cause. Individuals must recognize that expectations do not always translate into desired results, and mental preparedness is essential for managing setbacks. A lack of such preparedness can lead to severe psychological consequences, including anxiety, depression, and suicidal tendencies. This study examines coping strategies for managing the psychological impact of unmet expectations in various high-stakes scenarios, such as academic performance, relationships, and career goals. Coping mechanisms are influenced by situational factors, environmental conditions, and available support systems. By analyzing these variables, the study aims to provide practical strategies for resilience-building. A key focus of this study is the concept of multiple expectation sources—a framework that encourages individuals to diversify their goals and aspirations. By generating multiple pathways for success, individuals can mitigate the psychological burden of a single failed expectation. This approach brings adaptability, it ensures that setbacks in one domain do not lead to complete emotional breakdowns. Overall, this research contributes to understanding the psychological resilience needed in high-risk, high-expectation environments. It offers insights into preventative measures for emotional distress, physical burnout, and mental exhaustion. By equipping individuals with strategic decision-making skills, clarity of thought and backup planning methods, this study aims to promote long-term psychological well-being and adaptive coping strategies.
Keywords: coping mechanisms; expectations; gender perspectives; psychological adaptations; resilience; risk analysis; self-esteem; trauma